PENERAPAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH UNTUK MENINGKATKAN KEAKTIFAN PADA PEMBELAJARAN IPS MATERI MASALAH-MASALAH SOSIAL DI LINGKUNGAN SETEMPAT KELAS IV SDN 5 CIKIDANG - Aulia, Gadis Meirina (2014)
Penelitianini di latarbelakangiberdasarkanhasilobservasiawalpenelitian di kelas IV SDN 5 CikidangKecamatanLembangKabupaten Bandung Barat, terdapatmasalahpada proses pembelajaransiswa, salahsatunyarendahnyakeaktifansiswapadapembelajaran IPS materimasalah-masalahsosial di lingkungansetempatkarenadalamproses pembelajaranhanyaberpusatpada guru (teacher centered) denganmengandalkanbahanbelajardaribuku IPS (TextBook) yang tersediatanpamenggunakan model dan media pembelajaran. Hal inimenyebabkansiswabosandanbanyaksiswa yang kurangmemperhatikan guru.Sehinggaterbuktihanyasekitar 2 siswaatau 14 % siswa yang aktifdari 14 siswa.Untukmengatasimasalahtersebutpenelitimemperbaikikeaktifansiswadalam proses pembelajaranmelaluipenerapan model cooperative learningtipemake a match, akanmenciptakansuasanapembelajaran yang aktifdansiswaberpartisipasisecaralangsungdalam proses pembelajaran. Berdasarkanpermasalahandiatas, instrumenpenelitian yang digunakanlembarobservasikeaktifansiswa, aktivitas guru dandokumentasiberupafotodan video.Metodepenelitian yang digunakanadalahPenelitianTindakanKelas (PTK) yang berlangsung 3 siklus. Dari setiapsiklusnyapresentasekeaktifansiswadalam proses pembelajaranmengalamipeningkatan yang signifikanyaitupadatahapsiklus I 57% rata-ratanya 54,5, siklus II 85% rata-ratanya 76,7 dansiklus III 92% rata-ratanya 83. Jadikesimpulannyaadalahpenerapan Model Cooperative LearningtipeMake a MatchPadaPembelajaran IPS MateriMasalah-masalahSosial di LingkunganSetempatKelas IV SDN 5 Cikidangsangatefektifdalammeningkatkankeaktifansiswaterlihatpadasiklus III yang mencapai 92%. Sebagairekomendasibagisemuapihak yang terkaitdenganduniapendidikan, bahwa model cooperative learningtipemake a matchdapatdijadikanalternatifuntukmeningkatkankeaktifansiswapadapembelajaran IPS, karena model pembelajaraninimemilikikelebihan yang efektif, namundalammenggunakan model cooperative learningtipeMake a Matchbanyak yang perludipersiapkandenganmatang. The background of this research is based on the observation of the initial background research on SDN fourth grade 5 Cikidang District Lembang West Bandung regency, there are problems in the learning process of students, one of which is the low activity of students in social studies learning material social problems in the local environment due to the learning process only teacher-centered (teacher centered) by relying on the material learned from the book IPS (textbooks) are available without the use of models and instructional media. This leads to bored students and many students are less concerned teacher. So it proved to be only about 2 students or 14% of students are active from 14 students. To overcome this problem researchers improve the activity of students in the learning process through the implementation of cooperative learning model of the type of make a match, will create an atmosphere of learning that students participate actively and directly in the learning process. Based on the above problems, the research instrument used observation student activity sheets, teacher activities and documentation in the form of photos and videos. The research method used was Classroom Action Research (CAR), which lasted 3 cycles. Of each cycle the percentage of active students in the learning process experienced a significant increase in the phase of the first cycle is 57% on average 54.5, 85 second cycle averaged 76.7% and 92% the third cycle averages 83. So the conclusion is implementation of cooperative learning model type Make a Match on Social Learning Materials Social issues in Local Environment Class IV SDN 5 Cikidang very effective in increasing student activity seen in the third cycle is 92%. As a recommendation for all parties associated with the world of education, that the cooperative learning model of the type of make a match can be used as an alternative to increase the activity of students in learning social studies, because this model has the advantages that effective, but in using the model of cooperative learning many types Make a Match that need to be prepared carefully.